Thin-Film Engineering of Solution Processable N-Type Silicon Phthalocyanines for Organic Thin-Film Transistors - Cranston, Rosemary (Université d'Ottawa | University of Ottawa, 2024)
Despite significant advances in the field of organic electronic devices, there remains a critical need for soluble, stable, and high performing n-type organic semiconductors. Understanding how molecular design and thin-film fabrication conditions impact the formation, microstructure, morphology, and electronic properties of thin-films is crucial to expanding the application of organic thin-film transistors (OTFTs) in commercial electronics. Axially substituted silicon phthalocyanines (SiPcs) are promising organic electronic materials as a result of their favourable intermolecular stacking, crystallinity, chemical versatility, and compatibility with solution fabrication techniques. Here, SiPc derivatives with axial substituted alkyl chains of varying length, symmetry, and branching position were studied in OTFTs, establishing relationships between molecular structure, film morphology and device performance. Through low surface energy dielectric modifications, and the exploitation of fluorine-fluorine interactions at the dielectric-semiconductor interface, SiPc films with large area crystalline domains were achieved, yielding improved OTFT performance. Differences between sublimation and solution deposition methods were further investigated to understand the nucleation, crystallization, and film formation processes of SiPcs. Using a scalable high throughput printing platform for thin-film deposition highlighted the challenges of transitioning from lab scale fabrication to techniques compatible with commercial manufacturing. Finally, fabrication parameters play an important role in thin-film formation and resultant OTFT performance, with key parameters such as deposition rate, time, solvent, temperature, and post fabrication processing identified, examined, and controlled to obtain high performing devices. The works presented herein demonstrate the effectiveness of molecular substitutions and fabrication tuning as strategies to control crystal packing and the charge transport properties of semiconducting molecules, furthering our understanding of solution processable n-type semiconductors.